IMPLEMENTASI BIMBINGAN DAN KONSELING ISLAMI DALAM MENANGANI PROBLEMATIKA PESERTA DIDIK DI SEKOLAH - Sukatin; Siti Khofifah Lailatun Najwa; Kunti Fadhilah; Nurul Hidayani; Nur Aini (INOVASI : Jurnal Ilmiah Pengembangan Pendidikan, 2026)
Islamic guidance and counseling is a strategic effort to assist students in overcoming various problems encountered in the school environment. This approach emphasizes the internalization of Islamic values derived from the Qur’an and Hadith in the guidance and counseling process. This study aims to describe the implementation of Islamic guidance and counseling in addressing students’ problems at school. The research method used is qualitative with a library research approach by reviewing relevant literature, journals, and scientific sources related to the topic. The results indicate that Islamic guidance and counseling plays an important role in helping students understand themselves, manage emotions, improve social skills, and develop a balanced personality in both worldly and spiritual aspects. The implementation of Islamic guidance and counseling is carried out through several stages, namely analysis, synthesis, diagnosis, prognosis, and counseling, all of which are based on Islamic values. Therefore, Islamic guidance and counseling can be an effective solution in handling students’ problems and supporting the achievement of holistic educational goals.